2013
DOI: 10.1002/cbin.10071
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of HGF in BMMSCs by baculovirus‐mediated transduction

Abstract: Bone marrow-derived mesenchymal stem cells (BM-MSCs) transplantation is widely adopted for the curing of osteonecrosis of femoral head (ONFH) in recent years. Furthermore, it is known that introducing hepatocyte growth factor (HGF) into BM-MSCs will greatly improve the therapeutic effect of stem-cell therapy owing to the great angiogenic and anti-fibrotic capabilities of HGF. However, continuing overexpression of HGF in vivo may cause sarcomas, such as Kaposi's sarcoma. Aiming at enhancing the therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Its ability to stimulate mitogenesis, cell motility, and matrix invasion gives it a central role in angiogenesis, tumorogenesis, and tissue regeneration (Nakamura et al, 2011;Tu et al, 2013). In our study, transcripts of HGF where found significantly up-regulated in cells treated with NannoG in comparison to the control cells.…”
Section: Nannog Exhibits Skin Protection Properties By Mediating Oxidsupporting
confidence: 53%
“…Its ability to stimulate mitogenesis, cell motility, and matrix invasion gives it a central role in angiogenesis, tumorogenesis, and tissue regeneration (Nakamura et al, 2011;Tu et al, 2013). In our study, transcripts of HGF where found significantly up-regulated in cells treated with NannoG in comparison to the control cells.…”
Section: Nannog Exhibits Skin Protection Properties By Mediating Oxidsupporting
confidence: 53%
“…These findings suggest that UC-MSCs may secrete soluble factors that inhibit V γ 9V δ 2T cell proliferation. MSCs can secrete many factors, including transforming growth factor- β (TGF- β ) [ 30 ], hepatic growth factors (HGF) [ 31 ], prostaglandin E2 (PGE2) [ 30 ], IL-10 [ 30 ], indolamine 2,3-dioxygenase (IDO) [ 32 , 33 ], nitric oxide (NO) [ 30 ], heme oxygenase-1 (HO-1) [ 34 ], and human leukocyte antigen-G (HLA-G) [ 35 ], and TGF- β , IL-10, and PGE2 are potent inhibitors of T cell immunity [ 4 , 36 – 38 ]. These factors together with other unknown factors may act to inhibit T cell proliferation directly and indirectly.…”
Section: Discussionmentioning
confidence: 99%